Unbalanced rural development in underdeveloped areas: rurality and human settlements - Xueyi Wang; Manguo Geng; Xianglong Tang (Frontiers in Sustainable Food Systems)
IntroductionThe continuous migration of rural populations to urban areas poses a significant threat to food production and sustainable development in underdeveloped regions. Consequently, planning farmers’ livelihoods and optimizing their living environments are crucial for addressing rural challenges. Rurality represents the fundamental attributes of the countryside, serving as an accurate measure of the stages and characteristics of rural development and providing valuable support for policy formulation.MethodsIn this study, 87 counties (districts) in Gansu Province were selected as samples to construct and evaluate a rurality evaluation index system. The Geographical Detector Model and Pearson’s correlation analysis were applied to examine the relationship between the rurality index and key factors of the human settlement environment and identify pathways for rural development.ResultsThe findings demonstrated that the rurality index effectively reflects the spatiotemporal patterns of rural development, demonstrating a steady increase from west to east across Gansu Province. Various human settlement factors influence the spatial distribution of the rurality index, with humanities factors emerging as the primary drivers. Based on their dominant factors, the counties in Gansu Province were categorized into three groups for policy formulation: external economy-driven rural areas, endogenous resource-driven rural areas, and location-constrained rural areas.DiscussionHowever, it was also recognized that the rurality index alone does not comprehensively capture the current state of rural agricultural development. To propose effective, regional, and integrated rural development policies for underdeveloped areas, it is essential to combine agricultural development policies with an analysis of the existing rural living environment.